Pengaruh Efektivitas Penggunaan Sistem Informasi Akuntansi, Budaya Kerja, dan Insentif terhadap Kinerja Karyawan - Widhawati, Astri; Damayanthi, I Gst. Ayu Eka (E-Jurnal Akuntansi, 2018)
Sustainability and success of a company or organization can be seen from the performance owned by employees. Companies or organizations expect employees to complete tasks and produce information in a timely, accurate, and reliable manner. This study aims to determine the effect of the effectiveness of the use of accounting information systems, work culture, and incentives on employee performance. This research was conducted at Rural Bank (BPR) in Denpasar City. Determination technique of sample used in this research is purposive sampling technique. Respondents in this study are the internal supervisors, the credit and marketing division, the funding section, and the accounting department. Data collection was done by distributing questionnaires and interviews. Data analysis technique used is multiple linear regression analysis. The results of this study indicate that the effectiveness of the use of accounting information systems, work culture, and incentives have a positive and significant impact on employee performance.